INFLUENCE OF FAMILY FINANCIAL STATUS ON FEMALE STUDENTS’ RETENTION IN PUBLIC SECONDARY SCHOOLS IN MUKAA SUB-COUNTY, KENYA - Nzina, Jacinta W; Kimiti, Richard; Mulwa, David M. (Scholarly Research Journal for Interdisciplinary Studies, 2019)
Family financial status has been highlighted as of great importance in influencing the retention of female students in secondary schools globally. Thus the objective of this study was to establish the extent to which family financial status influence female students’ retention in public secondary school in Mukaa Sub-county, Kenya. The study was guided by the Systems Theory of Management. The study employed descriptive survey research design. The target population of the study comprised of 37 principals, 50 form four class teachers and 1,240 form four female students in public secondary schools in Mukaa Sub-county. Questionnaires and documentary analysis were used to collect the data. The quantitative data was coded and entered using SPSS version 24 computer software. Descriptive statistics specifically, percentages and frequencies were used for analyze data. The results of the study revealed that family financial status influence female students’ retention to a great extent as indicated by 72.7% of the teachers and 54.5% of the principal respondents. Based on the study findings, it was concluded that most female students drop out of school because of their parents’ poor financial status This study recommends that the Government of Kenya should review bursary policies for needy students and increase funding in secondary schools, communities should be empowered to alleviate poverty and enable families’ increase their income, Parents should be sensitized to fully understand the importance of completion of secondary education and school administrators should strengthen guidance and counseling department in secondary schools.
Keywords: Female students and Socio-economic factors.